Chapter Carbon Nanotube (CNT)-Reinforced Metal Matrix Bulk Composites: Manufacturing and Evaluation - Reinert, Leander (InTechOpen, 2016)
This chapter deals with the blending and processing methods of CNT-reinforced metal matrix bulk composites (Al/CNT, Cu/CNT and Ni/CNT) in terms of solid-state processing, referring mainly to the research works of the last ten years in this research field. The main methods are depicted in a brief way, and the pros and cons of each method are discussed. Furthermore, a tabular summary of the research work of the mentioned three systems is given, including the blending methods, sintering methods, the used amount of CNTs and the finally achieved relative density of the composite. Finally, a brief discussion of each system is attached, which deals with the distribution and interaction of the CNTs with the matrix material.